Midlife adiposity predicts cognitive decline in the prospective Multicenter AIDS Cohort Study. (16th July 2019) - Rubin, Leah H.; Gustafson, Deborah; Hawkins, Kellie L.; Zhang, Long; Jacobson, Lisa P.; Becker, James T.; Munro, Cynthia A.; Lake, Jordan E.; Martin, Eileen; Levine, Andrew; Brown, Todd T.; Sacktor, Ned; et al.
Abstract : Objective: Obesity is a common, modifiable cardiovascular and cerebrovascular risk factor. Among people with HIV, obesity may contribute to multisystem dysregulation including cognitive impairment. We examined body mass index (BMI) and central obesity (waist circumference [WC]) in association with domain-specific cognitive function and 10-year cognitive decline in men with HIV infection (MWH) vs HIV-uninfected (HIV−) men. Methods: A total of 316 MWH and 656 HIV− Multicenter AIDS Cohort Study participants ≥40 years at baseline, with neuropsychological testing every 2 years and concurrent BMI and WC measurements, were included. MWH were included if taking ≥2 antiretroviral agents and had HIV-1 RNA <400 copies/mL at >80% of visits. Mixed-effects models included all visits from 1996 to 2015, stratified by HIV serostatus, and adjusted for sociodemographic, behavioral, and clinical characteristics. At baseline and follow-up, 8% of MWH and 15% of HIV− men and 41% of MWH and 56% of HIV− men were ≥60 years, respectively. Results: Cross-sectionally, higher BMI was inversely associated with motor function in MWH and HIV− men, and attention/working memory in HIV− men. WC was inversely associated with motor function in MWH and HIV− men. Longitudinal associations indicated an obese BMI was associated with a less steep decline in motor function in MWH whereas in HIV− men, obesity was associated with a greater decline in motor function, learning, and memory. WC, or central obesity, showed similar patterns of associations. Conclusion: Higher adiposity is associated with lower cognition cross-sectionally and greater cognitive decline, particularly in HIV− men. Overweight and obesity may be important predictors of neurologic outcomes and avenues for prevention and intervention.